2022
DOI: 10.1097/mpg.0000000000003396
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Eosinophilic Esophagitis is Associated With Low Baseline Impedance

Abstract: Background and Aims:Eosinophilic esophagitis (EoE) is a chronic inflammatory disorder that requires repeat endoscopic evaluation(s) to assess response to treatment. This results in high health care costs and a procedural burden in affected children. Noninvasive alternate modalities to reassess disease activity have not been established. Low baseline impedance measured by multichannel pH impedance (pH-MII) is seen in adults with EoE, in keeping with poor mucosal integrity. We aimed to investigate the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…While the value of endoscopic impedance measurements may not add significant value at this time because pediatric gastroenterologists routinely take biopsies during endoscopies to make a mucosal diagnosis, their role may be as an alternative to endoscopy. Studies have shown that measuring nocturnal baseline impedance values during a 24‐h study, for example, may predict which patients have esophagitis 7–9 . Our study suggests that even placement of a probe for much shorter times could give impedance readings that could suggest the presence or absence of esophagitis and its distribution in the esophagus.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…While the value of endoscopic impedance measurements may not add significant value at this time because pediatric gastroenterologists routinely take biopsies during endoscopies to make a mucosal diagnosis, their role may be as an alternative to endoscopy. Studies have shown that measuring nocturnal baseline impedance values during a 24‐h study, for example, may predict which patients have esophagitis 7–9 . Our study suggests that even placement of a probe for much shorter times could give impedance readings that could suggest the presence or absence of esophagitis and its distribution in the esophagus.…”
Section: Discussionmentioning
confidence: 67%
“…Studies have shown that measuring nocturnal baseline impedance values during a 24-h study, for example, may predict which patients have esophagitis. [7][8][9] Our study suggests that even placement of a probe for much shorter times could give impedance readings that could suggest the presence or absence of esophagitis and its distribution in the esophagus.…”
Section: Ta B Lmentioning
confidence: 75%
“…Overall, mucosal impedance, measured with a variety of techniques, either ambulatory setting or single-channel and balloon-based, appears promising and may be able to differentiate GERD from EoE as well as track the histologic progression of EoE (151,(155)(156)(157)(158)(159). Currently, however, data regarding mucosal impedance measurements in EoE are limited.…”
Section: Esophageal Electrical Impedance Technologiesmentioning
confidence: 99%